Effects of Ball Sports on Future Risk of Stress Fracture in Runners - Fredericson, M.; Ngo, J.; Cobb, K. (Clinical Journal of Sport Medicine, 2005)
Objective: To evaluate whether playing ball sports during childhood and adolescence is associated with the risk of stress fractures in runners later in life.